Gene Expression Profiling of Trematomus bernacchii in Response to Thermal and Stabling Stress - Samuele Greco; Anastasia Serena Gaetano; Gael Furlanis; Francesca Capanni; Chiara Manfrin; Piero Giulio Giulianini; Gianfranco Santovito; Paolo Edomi; Alberto Pallavicini; Marco Gerdol (Fishes, 2022)
The Antarctic continent is one of the most pristine environments on planet Earth, yet one of the most fragile and susceptible to the effects of the ongoing climate change. The overwhelming majority of the components of Antarctic marine trophic chain are stenotherm organisms, highly adapted to the extreme, but extremely stable, freezing temperatures of the Antarctic ocean, which have not changed significantly during the past fifteen million years. Notothenioid fishes are the most abundant representatives of ichthyofauna at these latitudes, being ubiquitously found in coastal areas across the entire continent. While different Antarctic fish species have been previously subjected to studies aimed at defining their range of thermal tolerance, or at studying the response to acute thermal stress, just a handful of authors have investigated the effects of the exposure to a moderate increase of temperature, falling within the expected forecasts for the next few decades in some areas of the Antarctica. Here, the emerald rockcod Trematomus bernacchii was used as a model species to investigate the effects of a 20-day long exposure to a +1.5 °C increase in the brain, gills and skeletal muscle, using a RNA-sequencing approach. In parallel, the experimental design also allowed for assessing the impact of stabling (including acclimation, the handling of fishes and their confinement in tanks during the experimental phase) on gene expression profiling. The results of this study clearly identified the brain as the most susceptible tissue to heat stress, with evidence of a time-dependent response dominated by an alteration of immune response, protein synthesis and folding, and energy metabolism-related genes. While the gills displayed smaller but still significant alterations, the skeletal muscle was completely unaffected by the experimental conditions. The stabling conditions also had an important impact on gene expression profiles in the brain, suggesting the presence of significant alterations of the fish nervous system, ...